Prosthetic mitral valve thrombosis in a known case of rheumatic heart disease at 37 weeks pregnancy: a case report - Nahar, Kirty; Nahar, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Pregnancy with prosthetic valve is a challenging situation since this is a hypercoagulable state and maintenance of anticoagulation for prosthetic valves becomes difficult due to the teratogenic effects and altered pharmacokinetics of anticoagulant drugs. Despite adequate anticoagulation, the incidence of prosthetic valve thrombosis has been estimated as 4% to 14% during pregnancy. Management decisions for this life-threatening complication are complex. Open-heart surgery has a very high risk of maternal mortality and fetal loss, especially in early pregnancy. Furthermore, bleeding and embolic risks associated with thrombolytic agents, the limited efficacy of thrombolysis in certain subgroups, and a lack of experience in the setting of pregnancy raise important concerns. Mrs. X, a 36-year-old, gravida 3, para1+1 with 37 weeks pregnancy presented at Apollo hospitals, Ahmedabad in emergency department with complaints of severe dry cough and breathlessness for 24 hours. On through workup, she was diagnosed as mitral valve thrombosis in a known case of rheumatic heart disease post mitral valve replacement at 37 weeks pregnancy with late onset fetal growth restriction. After multi-speciality consultation she underwent thrombolytic therapy followed by high-risk emergency caesarean section. She delivered healthy male child, weight 2.21 kg and was discharged on 4th post-op day. Management of pregnant patients with mechanical valves is complex, especially when valve thrombosis and other complications occur. Multidisciplinary approach is essential and, in this case, led to successful maternal and foetal outcome.